Conflict of laws in Italy : the text and an English translation of Italian Law No. 218 of May 31, 1995 (Reform of the Italian System of Conflict Laws) : the international conventions referred to in the law /: the text and an English translation of Italian Law No. 218 of May 31, 1995 (Reform of the Italian System of Conflict Laws) : the international conventions referred to in the law. (1997) - Unknown
No abstract available